Alteration of Mother’s Sexual Activity during Pregnancy - Erni Samutri; Wenny Artanty Nisman; Wiwin Lismidiati (Alma Ata University Press, 2020)
Sexual activity during pregnancy is one of the significant issues for both pregnant mother and healthcare provider, though rarely disclosed. Studies on this topic have been done broadly, though still no conclusion. The aim of this study was to analyze the change of mother’s sexual activity before and during pregnancy and to describe resources used by mother to find sexual activity information. A descriptive cross sectional study was conducted on pregnant mothers who undergo antenatal care at Tegalrejo public health center, Yogyakarta. Sample was determined using quota sampling which total sample was 78 pregnant mothers (26 pregnant mothers per trimester) without significant health problem related to their pregnancy, such as high risk pregnancy condition and vaginal bleeding. Data were collected using Indonesian version of Pregnancy Sexuality and Response Inventory (PSRI) questionnaire which reliable to used (Cronbach’s alpha: 0.714). Data on sexual activity (biological, emotional, and physical aspects) in each trimester were analyzed by paired t test. Data on sexual activity among trimesters in several sub-aspects (frequency, desire, and pain during intercourse) were analyzed by Kruskal wallis and followed by post hoc analysis on significant result. Result showed the significant changes of biological aspect of mother’s sexual activity before and during pregnancy, especially in the second (p 0.002) and third trimester (p 0.000) and the changes tend to decline. Significant decline also found in emotional aspect of all trimesters (p<0.05). In line with biological aspects, physical aspect also showed significant decline in the second (p 0.000) and third trimester (p 0.000). Pregnant mother got numerous resources related to sexual activities during pregnancy, yet the most common was from healthcare provider (35.9%). Providing the right information related to this topic will help the mother to understand their sexual activity changes and to choose the right decision in performing sexual activity.